Conditioned pain modulation elicited through manual pressure techniques on the cervical spine: a crossover study - René Castien; Roland R. Reezigt; Ruben den Hartog; Andreas Amons; Willem De Hertogh; Gwendolyne G. Scholten-Peeters (PAIN Reports)
Abstract. Introduction:. Manual pressure techniques are commonly employed as a therapeutic approach for individuals experiencing musculoskeletal pain. The painful nature of these techniques suggests that a central mechanism known as conditioned pain modulation (CPM) might play a role. Objectives:. This study tested whether a painful manual pressure technique (MPT) reduces pain sensitivity partly by eliciting a CPM effect. Methods:. This crossover study examined 3 different conditioning stimuli: (1) a cold pressor test (CPT) with the contralateral hand submerged in a cold water bath, (2) painful MPT, and (3) sham-MPT on suboccipital muscles. We measured their effect on pain sensitivity using pressure pain thresholds at 3 locations: locally (suboccipital muscles), regionally (trapezius muscle), and remotely (tibialis anterior muscle). Results:. In 63 healthy participants, no significant differences were found between the painful MPT and CPT on the pressure pain thresholds at all test locations: locally, −11 kPa (95% CI: 3 to −25); regionally, −15 kPa (95% CI: 10 to −39); and remotely, −24 kPa (95% CI: 55 to −7). Manual pressure technique compared to sham-MPT showed significant differences in the suboccipital muscles, −20.04 kPa (95% CI: −6.45 to −34.63) and the trapezius muscle, −38.24 (95% CI: −13.97 to −62.5) but no significant difference at the tibialis anterior muscle, −17.5 kPa (95% CI: 13.9 to −48.91). Conclusion:. Painful MPTs applied at the suboccipital muscles reduce pain sensitivity at all sites, similar to the CPT, indicating CPM activation. Central pain inhibition might contribute to the effect of painful MPT in healthy people.